APPLICATION OF TEAM GAMES TOURNAMENT (TGT) TYPE COOPERATIVE LEARNING MODEL TO IMPROVE LEARNING OUTCOMES OF PPKN CLASS V AT SD NEGERI 48 LUBUKLINGGAU - Era Sintia (Teaching and General Education Studies, 2025)
The learning process of Pancasila and Citizenship Education (PPKn) in elementary schools is often dominated by conventional, teacher-centered methods, resulting in low student participation and learning outcomes. This condition was also observed in Grade V students at SD Negeri 48 Lubuklinggau. To address this issue, a more engaging and interactive learning model is needed—one that promotes cooperation, active involvement, and motivation. This study aims to determine the effectiveness of the Team Games Tournament (TGT) type cooperative learning model in improving PPKn learning outcomes. The research employed a quantitative approach using a quasi-experimental method with a one-group pre-test and post-test design. The subjects were 21 Grade V students. Data collection involved multiple-choice tests conducted before and after the treatment, as well as observations of student learning activities. The results showed that the average pre-test score of 50.40 increased to 80.50 in the post-test. Additionally, the number of students who met the Minimum Completeness Criteria (KKM) rose from 9 to 19 students. These findings confirm that the TGT learning model is effective in enhancing student learning outcomes and fostering collaborative, competitive, and enjoyable learning experiences. In conclusion, the TGT model can serve as an effective strategy for improving learning outcomes in theoretical subjects like PPKn. Practically, it offers teachers an innovative alternative to reduce student disengagement. Academically, the model holds potential for further development. Future studies are recommended to integrate TGT with digital tools or apply it in different subjects and education levels to evaluate its broader impact.